Emerging Trends in Pet Food: Scientific Innovations, Patent Landscapes, and Global Market Development - Vuthisopon, Sujira; Kamonpatana, Pitiya; Promhuad, Khwanchat; Srisa, Atcharawan; Wongphan, Phanwipa; Seubsai, Anusorn; Klinmalai, Phatthranit; Harnkarnsujarit, Nathdanai (My University, 2026)
The pet food sector has progressively evolved over the past decade from conventional nutrition toward functionally targeted and sustainability-oriented systems that are increasingly parallel developments in human health. While numerous reviews have examined individual aspects of pet food innovation, an integrated perspective linking scientific research, patent activity, and global market dynamics remains limited. This review addresses this gap by systematically synthesizing peer-reviewed literature, patent landscapes, and product launch data to identify key drivers and bottlenecks shaping contemporary pet food innovation. The analysis highlights a strong concentration of research and patent activity in health-oriented functional formulations, particularly those targeting gastrointestinal health, immune modulation, and age-related conditions, while postbiotics, precision nutrition, and digital tools remain comparatively underdeveloped. Sustainability-driven ingredients and alternative proteins show growing momentum but face persistent challenges related to scalability, regulation, and sensory acceptance. The commercial success of functional pet foods depends on translating scientific findings into stable, manufacturable, and evidence-supported products. Future innovation will therefore be shaped by technologies that connect biological function with process feasibility and market readiness. This review concludes that future progress in pet food innovation will depend on integrated frameworks that align biological efficacy, technological feasibility, and market viability, thereby bridging the gap between scientific advancement and commercial implementation.
Keywords: canine; companion animals; feline; functional; pet food